Study of Satisfaction of Staff working Central Sterile Supply Department of a Tertiary care Teaching hospital - Malhotra, Monica; Kumar, Sunil (Innovative Journal of Medical and Health Sciences, 2021)
Impact of nosocomial infections ranges from increased length of hospital stay, emotional stress, disability, death of the patients as well as increased hospital cost for the patients and providers. Studies in India have reported nosocomial infection rates from 8% to 58 %. The observations of staff working in SKIMS Central Sterile Supply Department of various cadres revealed that 50 % of the staff were in the age group 20-40 and 50 % of staff was of age group > 40 years of age, and maximum 92% of staff are Male. Education Qualification wise it was found that most of 50% staff is 12th pass. The results of the study indicate that higher percentage of motivation and job satisfaction among the staff working in Central Sterile Supply Department are attributable to working hours, in-service training, reward/appreciation, and resting time during work and satisfied with supervisory and subordinate staff.